Analisis Karakteristik Kondisi Fisik Pemain Sepak Bola Berdasarkan Posisi Bermain - Safri Irawan; Meri Haryani; Agung Prasetyo; Arief Ibnu Haryanto; Rifky Mile; I Kadek Suardika; Rosita Gani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the physical characteristics of soccer players based on their playing position through a literature review approach. The method used is a review of various scientific articles discussing the physical demands of soccer players in terms of the positions of goalkeeper, defender, midfielder, and striker. The results of the study indicate that there are clear differences in the characteristics of physical conditions in each position. Midfielders tend to have the most dominant endurance due to the high demands of mobility during matches. Strikers excel in aspects of speed and explosive power that support explosive movement in attacking situations. Defenders prioritize physical strength to face duels and maintain defensive stability, while goalkeepers have special characteristics such as reaction time, agility, and coordination.